LITTERA SCRIPTA MANET. - HINE, DARYL (Yale Review, 2012)
The poem "Littera Scripta Manet" by Daryl Hine is presented. First Line: From salutary opening to complimentary close; Last Line: Must come as an inscrutable disguise.